PEERLINK: A Comprehensive Collaborative Platform - Viraj More; Ms.P.R. Patil; Divyesh Dhole; Tejas Patil; Chetan Dhangar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In the digital age, real-time collaboration tools have become essential for software development, enabling teams to work together seamlessly across geographical boundaries. This paper introduces PeerLink, an innovative real-time collaborative code editor designed to enhance the programming experience by integrating coding, communication, and collaboration into a single platform. Built with modern web technologies such as Vite, React, and Socket.IO, PeerLink offers a responsive and interactive user interface that supports multiple programming languages, real-time code synchronization, and execution. The platform’s architecture leverages WebRTC for video communication, allowing users to engage in face-to-face interactions while coding collaboratively. PeerLink’s server-side, developed with Express, manages user connections and synchronizes code changes, ensuring all participants have the latest updates. The system also incorporates state persistence, maintaining language preferences and code across sessions. This paper explores the design and implementation of PeerLink, highlighting its potential to transform collaborative coding practices by providing a comprehensive environment for developers. By addressing challenges in real-time collaboration, such as synchronization and user experience, PeerLink aims to enhance productivity and foster a more connected developer community. The findings and insights from this study contribute to the growing body of research on collaborative software development tools.